Application of anhysteresis residual magnetization method to evaluate distribution of additional plastic deformation in ferromagnetic metals - Shigeo KOTAKE (The Japan Society of Mechanical Engineers, 2016)
After a huge earthquake, it is important to evaluate additional plastic deformation induced by the disaster to identify damage to important structures such as nuclear power plants, tall buildings, or high-pressure hydrogen infrastructure. As residual magnetization takes on anhysteresis characteristics during plastic deformation, the “law of approach” based on the magnetomechanical functional property can be used as a non-destructive test, termed anhysteresis residual magnetization method, to determine additional plastic deformation beyond that of the last instance of magnetization or demagnetization. The mechanism of this property can be explained by the interactions between dislocations and magnetic domain walls. Furthermore, the experimental results of demagnetization under tensile or compressive stress are provided for the anhysteresis residual magnetization method under a non-magnetic field. The advantages and limitations of the method are discussed.